Risk Factor Analysis in Vascular Access Complications for Hemodialysis Patients - Cristian Dan Roşu; Sorin Lucian Bolintineanu; Bogdan Florin Căpăstraru; Roxana Iacob; Emil Robert Stoicescu; Claudia Elena Petrea (Diagnostics)
Background: Chronic kidney disease (CKD) and renal failure remain critical global health challenges, with vascular access complications posing significant obstacles in hemodialysis management. Methods: This study investigates the early and late complications associated with vascular access procedures in a cohort of 1334 patients from Timiș County Emergency Clinical Hospital. Patients were categorized into early complications, occurring within 30 days postoperatively, and late complications, developing beyond this period. Demographic data, comorbidities, and lifestyle factors, including age, gender, body mass index (BMI), smoking status, hypertension, diabetes, and cardiovascular disease (CVD), were recorded and analyzed. Early complications included thrombosis, hemorrhage, edema, and non-maturation, while late complications involved thrombosis, aneurysmal dilation, venous hypertension, and infections. Results: Hemorrhage (32.3%) and thrombosis (30.8%) were the most prevalent early complications, influenced significantly by diabetes and hypertension. Non-maturation showed a strong association with diabetes and cardiovascular disease (odds ratio: 1.70). For late complications, thrombosis was most frequent, with hypertensive patients exhibiting increased risk (relative risk: 1.18). BMI was a significant factor in both early and late complications. Risk analysis using odds ratios and relative risks revealed distinct patterns of complication risks based on comorbidities and smoking status. Logistic regression modeling for thrombosis demonstrated moderate predictive accuracy (AUC: 0.64). Conclusions: These findings suggest that clinical interventions, such as stricter perioperative glycemic and blood pressure control, and personalized surgical strategies for patients with high BMI or comorbidities, could significantly reduce the incidence of vascular access complications and improve outcomes in this high-risk population.